Combined Effects of Particle Shape and Deformability on Cyclic Shear Response of Sand-rubber Mixtures - Ari, Abdulmuttalip; Akbulut, Suat (BUDAPEST UNIV TECHNOLOGY ECONOMICS, 2026)
In this study, the cyclic response of sand-rubber mixtures was investigated in terms of shape and deformability effects of particles. A series of cyclic simple shear tests were performed using three different sand and two different rubber specimens. The rubber particles were included in the sand samples with five different contents, and the mixtures were loaded until five different shear strain levels. The cyclic response was evaluated using secant shear modulus and damping ratio parameters. The particle deformability and shape effects of the rubber particles were elaborated using local images from the tests. In addition, the mixtures were subjected to California bearing ratio test to correlate the cyclic response with static behavior. The results were evaluated by adopting an interactive approach by considering the shape and deformability of the particles together. It was revealed that the influence of shape and rubber content on the cyclic parameters were found to be highly dependent on the shear strain level. The shear modulus at small strain levels followed similar trends as the bearing ratio in terms of particle shape and rubber content influences. The contribution of sand and rubber particles to the damping ratio varied with the shear strain, and particle shape effects emerged at large strain levels. The local image of the samples reveals that the response of the mixtures is transformed as the rubber particles produce primary force columns. Rubber particles can provide a fiber effect depending on the shape features.
Keywords: particle shape; particle deformability; sand; rubber; shear modulus; damping ratio; DYNAMIC PROPERTIES; BEHAVIOR; Engineering